HUBUNGAN PERSONAL HYGIENE TERHADAP KEJADIAN PIODERMA PADA PEMULUNG DI TEMPAT PEMBUANGAN AKHIR (TPA) TERJUN KECAMATAN MEDAN MARELAN - DIAH INDAH ARIZKA; HERVINA . (JURNAL ILMIAH KOHESI, 2021)
Personal hygiene is an activity undertaken to maintain personal health in preventing infectious diseases.Maintain personalhygiene to reduce the occurrence of skin diseases due to infection, one of which is a bacterial infection. The most commonbacterial infection is pyoderma. To determine the relationship between personal hygiene with the occurrence of pyoderma onlandfill scavengers at Terjun Subdistrict Medan Marelan district. This study was an descriptive analitic using cross sectionaldesign. The results were analyzed using Chi-square. The Population in this research were 107 Scavengers. The samplingresult is done by randomized sampling method. Data collection uses a questionnaire consisting 15 questions, then all of thesample will get examination of lesions on the skin. The proportion of pyoderma incidence was 49 respondents. Statistical testshowed that the p value was under 0,05. Skin p=0,004; Hands, nail and foot p=0,000; Hair p=0,000 and it means thatpersonal hygiene affected the incidence of pyoderma. There was a significant correlation between personal hygiene to theincidence of pyoderma on landfill scavengers at Terjun Subdistrict Medan Marelan district.